Israeli-Palestinian Conflict Beyond Resolution: A Critical Assessment - Fadhila Inas Pratiwi; M. Aryo Rasil Syarafi; Demas Nauvarian (Faculty of Social and Political Sciences, Universitas Gadjah Mada, 2022)
Of all the inter-state conflict currently happening in different regions of the world, the Israel- Palestine conflict has stood the test of time to become one of the longest and most impactful. Despite numerous attempts to resolve the Israeli-Palestinian conflict, both parties have persisted, mainly showing a lack of compromise and commitment. This paper aims to analyze the underlying reason to the various unsuccessful attempts of Israel-Palestine conflict resolutions. This paper argues that there are four core issues that become object of negotiation in each attempt: borders, security, Jerusalem, and refugees. This paper assesses each party’s stances on these four issues and how they shape the negotiation process. This is done through an empirical generalization by inductive methodology, using library studies as a data collection method. This paper concludes that there should be an ideational change to compromise within the domestic politics of both parties to make future conflict resolution possible.